History of coman-kipchaks study in pre-revolutionary and soviet literature: peculiarities of research (Journal of history, 2017)
Main purpose of this research is to identify the peculiarities of the works, studying political, ethnic history, culture, religion and language of the Coman-Kipchak. Works that were published on the research topic are systematized to pre-revolutionary and Soviet period.Based on the analysis of written historical sources and ethnographic materials of the pre-revolutionary period, it was concluded that the Coman, Kipchak and Kimek tribes are related to each other. Based on the study of congeneric composition and language affiliation of the Kipchaks, influence of the Kipchak component on the ethnic history of the Turkic-speaking people, such as: Kazakhs, Uzbeks and Bashkirs, was discovered.During the early Soviet period, scientific research was based on the marxist-leninist methodology, and works of this period mostly contained negative assessment of the nomadic people history. The main achievement in Kipchakology was the introduction of written scientific sources. On the basis of written sources, the congeneric composition of the Kipchak alliances, territory, culture, world views, history of relations with neighboring nations was studied.The methodological basis of this work was guided by traditional scientific methodologies of historiographical research, such as: historiographic analysis, historical concepts and conclusions on the topic. And also, the civilizational approach, widely used in modern historical science, proving the value of all cultures, despite the area of ​​origin, expansion and development. This historiographic research provides an opportunity to identify previously unexplored sides in the Kipchakology and work further in the identified areas.